Clinicoradiologic Predictors of Outcome of Posterior Fossa Extradural Hematoma: An Institutional Experience - Sobti, Shivender; Bansal, Sondev; Choudhary, Ajay; Gupta, Laxmi Narayan (Indian Journal of Neurotrauma, 2017)
Introduction Posterior fossa extradural hematomas (PFEDH) comprise 4 to 7% of all intracranial extradural hematomas (EDHs).Material and Methods A prospective study of 25 patients who presented with PFEDH was conducted in PGIMER, Dr. Ram Manohar Lohia (RML) Hospital, New Delhi in department of neurosurgery from January 2011 to July 2012. The patients were analyzed in relation to age, sex, mode of injury, Glasgow coma scale (GCS) at the time of presentation, computed tomography findings of the head, and therapeutic outcome. Duration of follow-up was 6 months.Results In the authors’ study, male-to-female ratio was 22:3. Age range was 6 months to 62 years and mean age was 23.70 years. Mode of trauma was fall from height in 12 patients, road traffic accident (RTA) in 12, and assault in 1. Most patients had acute course (80%) followed by subacute course (20%). GCS was between 8 and 15. Fracture was associated in 21 patients out of 25. Associated intracranial injury was present in 22 patients.Conclusion In this series, PFEDH is a result of direct impact injury as 88% of patients had overlying fracture. PFEDH should be suspected in patients who have got external injury to the occiput as it is commonly associated with formation of extradural hematoma in the posterior fossa. The neurologic status and outcome were associated with GCS, volume of hematoma, and associated intracranial injury. PFEDH rarely occurs as an isolated injury.
Keywords: extradural hematoma; posterior fossa extradural hematoma; computed tomographic scan; Glasgow coma scale; Glasgow outcome scale